Study for restoration ability in cytoplasmic male sterile system in Indian mustard [Brassica juncea (L.) Czern & Coss.] - Ashutosh Kumar* N.P. Yadav and K. Kumar (Electronic Journal of Plant Breeding, 2014)
Two cms lines of Moricandia viz., CMSNDRE-4 and CMS Mori were crossed with 30 genotypes to identify restorers and maintainers. Effective restorers for two CMS lines i.e., CMSNDRE-4 and CMS Mori could not be identified through Moricandia CMS system. However, common partial restorers were found in the parents, NPJ-147, NPJ-112, PRE-2007-06, NPJ-135, Divya-33, DRMREJ-2010-01, NPJ-148, DRMREJ-2010-02, Divya-22, R.H-919, RRN-693 and Kranti for both CMS lines. Effects of CMS lines on seed yield and its components traits indicated that seed yield in F1‟s were higher than the parents. The overall performance of F1‟s over both the standard variety viz., Kranti (SV1) and Maya (SV2) in seed yield showed yield depression as a result of negative cytoplasm interaction.